Transcranial direct current stimulation combined with exercise therapy for chronic low back pain: a systematic review and meta-analysis - Xia, Rui; Lu, Shihan; Zhao, Lunan (Frontiers in Human Neuroscience, 2026)
BackgroundChronic low-back pain (CLBP) is a leading cause of disability, with current treatments offering only modest benefits. Transcranial direct-current stimulation (tDCS) may enhance exercise therapy by modulating cortical excitability and pain-inhibitory pathways. This systematic review and meta-analysis quantified the additive effect of combining tDCS with structured exercise in adults with CLBP.MethodsWe searched PubMed, Web of Science, CENTRAL, Embase, and CNKI up to 25 September 2025. Randomized controlled trials (RCTs) comparing active tDCS plus identical exercise therapy vs. sham tDCS plus the same exercise in adults with CLBP (≥ 12 weeks) were included. Risk of bias was assessed using Cochrane RoB 2.0. Weighted mean difference (WMD) and standardized mean difference (SMD) were calculated for pain and function, respectively.GRADE was used to assess certainty.ResultsFive RCTs (n = 195) were included. For pain intensity (4 studies, n = 173), tDCS showed a significant additive effect (WMD = −0.99, 95% CI: −1.68 to −0.31, p = 0.006, I2 = 60.1%). For physical function (five studies, n = 195), the effect was favorable but non-significant (SMD = −0.65, 95% CI: −1.87 to 0.57, p = 0.28, I2 = 90.7%). Meta-regression indicated intervention duration significantly moderated functional outcomes (β = 0.56, p < 0.001). GRADE certainty was moderate for pain and low for function.ConclusionAnodal tDCS combined with exercise provides a modest but significant additional reduction in pain intensity for CLBP. Longer intervention duration may enhance functional outcomes. Clinical significance should be interpreted cautiously. Larger, well-designed trials are needed to confirm these findings and optimize stimulation parameters.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251151315, identifier CRD420251151315.